2002
DOI: 10.1577/1548-8675(2002)022<0677:pafcow>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Population and Fishery Characteristics of White Bass in Four Large Missouri Reservoirs

Abstract: The population and fishery characteristics of white bass Morone chrysops were determined for four large Missouri reservoirs to help establish meaningful objectives for white bass fisheries. The growth of white bass in Table Rock and Bull Shoals lakes was faster and a higher proportion of fish were larger than 380 mm than in Pomme de Terre Lake and Lake of the Ozarks. Age-4 white bass exceeded 400 mm at Table Rock and Bull Shoals lakes and averaged about 370 mm in the other two. When gender differences in growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…Therefore, fishery objectives for short-lived species may focus on maximizing the harvest of quality-length individuals. Previous studies evaluating size structure of popular white bass fisheries have reported PSD values greater than 60% in Nebraska (Bauer 2002) and Missouri (Colvin 2002). Our modeling results indicate that similar PSD values could be achieved while minimizing harvest reductions if strong year-classes of white bass occur every 3 years.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, fishery objectives for short-lived species may focus on maximizing the harvest of quality-length individuals. Previous studies evaluating size structure of popular white bass fisheries have reported PSD values greater than 60% in Nebraska (Bauer 2002) and Missouri (Colvin 2002). Our modeling results indicate that similar PSD values could be achieved while minimizing harvest reductions if strong year-classes of white bass occur every 3 years.…”
Section: Discussionsupporting
confidence: 58%
“…We selected three sport fishes with contrasting life histories to examine how the frequency of strong year-classes affects fishery characteristics. White bass Morone chrysops represented short-lived species, for which typical longevity is less than 5 years (Muoneke 1994;Colvin 2002;Guy et al 2002;Lovell and Maceina 2002;Willis et al 2002) and annual mortality is high (≥50%; Muoneke 1994;Colvin 2002;Schultz and Robinson 2002). We used largemouth bass to represent species of intermediate longevity, characterized by a typical life span of up to 10 years (Heidinger 1976;Carlander 1977) and mean annual mortality between 30% and 50% (Allen et al 2002;Bulak and Crane 2002;Driscoll et al 2007).…”
Section: Model Speciesmentioning
confidence: 99%
“…crappie, white bass, and yellow perch. The self-imposed length limits corresponded to sizes observed in other studies that assessed sizes of harvested fish (e.g., Colvin, 2002;Paukert et al, 2002;Isermann et al, 2005;Holley et al, 2009). For example, Isermann et al (2005) found that the mean minimum length of yellow perch harvested by anglers ranged from 21 to 26 cm, depending on the South Dakota lake assessed.…”
Section: Species 2010 2011supporting
confidence: 68%
“…In southern US, waters maximum age apparently is near age 7 (Colvin 2002;Lovell and Maceina 2002), although fish older than age-4 are rare (Muoneke 1994;Colvin 2002). Furthermore, white bass growth was below the statewide average at age 2 (Table 2), although direct comparisons are tenuous because we collected our SR sample in August, when the bass had completed a partial year of growth beyond age 2.…”
Section: Discussionmentioning
confidence: 99%